A prognostic index for extranodal marginal‐zone lymphoma based on the mucosa‐associated lymphoid tissue International Prognostic Index and serum β2‐microglobulin levels. (20th November 2020) - Kim, Hyung‐Don; Cho, Hyungwoo; Jeong, Hyehyun; Bang, Kyunghye; Kim, Shin; Lee, Kyoungmin; Kang, Eun Hee; Park, Jung Sun; Park, Chan‐Sik; Huh, Jooryung; Ryu, Jin‐Sook; Lee, Sang‐Wook; et al.
Summary: The mucosa‐associated lymphoid tissue (MALT) International Prognostic Index (IPI) was recently proposed as a prognostic index for patients with MALT lymphoma. We aimed to investigate the prognostic value of the serum β2‐microglobulin level in the context of MALT‐IPI, and we proposed a new prognostic index. Survival outcomes were analysed with regard to β2‐microglobulin level, MALT‐IPI, and the new prognostic index in MALT lymphoma patients ( n = 571). The validity of the new prognostic index was assessed using an independent cohort ( n = 216). Patients with high β2‐microglobulin levels had significantly worse progression‐free survival (PFS) and overall survival (OS) outcomes. A high β2‐microglobulin level was independently associated with poor PFS and OS. β2‐microglobulin levels further stratified patients in the MALT‐IPI intermediate‐risk group in terms of PFS and OS. A new prognostic index based on the MALT‐IPI and the β2‐microglobulin level, MALT‐IPI‐B, was proposed. The MALT‐IPI‐B was able to stratify patients into subgroups having distinct PFS and OS outcomes in both the training and validation cohorts. MALT‐IPI‐B enabled the identification of patients with poor survival outcomes who were classified into the intermediate‐risk group by the MALT‐IPI. In conclusion, this new β2‐microglobulin‐based prognostic index may have the specific advantage of identifying high‐risk patients who may require systemic treatment.